A two-ply artificial blood vessel of polyurethane and poly(L-lactide) - Pennings, A.J.; Knol, K.E.; Hoppen, H.J.; Leenslag, J.W.; van der Lei, B.
A biodegradable microporous small-caliber vascular prosthesis has been developed that consists of two layers. The inner layer has been made highly antithrombogenic by cross-linking of a mixture of linoleic acid and an alipharic polyetherurethane with dicumylperoxide. Microporosity was introduced by adding sodiumfluoride crystals of about 5 I~m in diameter prior to cross-linking and leaching them out afterwards. The outer ply has been constructed by precipitating a (95/5)physical mixture ofpolyesterurethane and poly(L-lactide)from solution in the presence of sugar crystals with dimensions in the range 30-90 t~m which were removed by exposing the graft to water. The two-ply grafts were tested in vivo by replacing I cm of the abdominal aorta of rats. All the grafts remained patent at least up to 1 year and did not exhibit any aneurismal formarion. The inner layer was covered with endothelial cells and several layers of smooth muscle cells.
Keywords: TWO-_PLY VASCULAR PROSTHESIS; BIODEGRADABLE; SALT-_LEACHING TECHNIQUE; CROSSLINKING; BLOODCOMPATIBLE; ANEURISM